The political determinants of government bond holdings. (May 2017) - Eichler, Stefan; Plaga, Timo
Highlights: We analyze the political factors of US government bond holdings. The dataset covers US investment in 60 countries in the period 2003–2013. In general, fewer political constraints and higher political stability attract US investment. In high risk countries, investors appreciate political constraints which make default difficult. In countries with high debt and sound institutions, investors appreciate few political constraints. Abstract: This paper analyzes the link between political factors and sovereign bond holdings of US investors in 60 countries over the 2003–2013 period. We find that, in general, US investors hold more bonds in countries with few political constraints on the government. Moreover, US investors respond to increased uncertainty around major elections by reducing government bond holdings. These effects are particularly significant in democratic regimes and countries with sound institutions, which enable effective implementation of fiscal consolidation measures or economic reforms. In countries characterized by high current default risk or a sovereign default history, US investors show a tendency towards favoring higher political constraints as this makes sovereign default more difficult for the government. Political instability, characterized by the fluctuation in political veto players, reduces US investment in government bonds. This effect is more pronounced in countries with low sovereign solvency.